Some Problems of Ultra-High-Speed Transportation Technologies - Skosar, V. Yu.; Burylov, S. V.; Dzenzerskyi, V. O. (Science and Transport Progress, 2023)
Purpose. The main purpose of the work is to identify some technical problems of high-speed transport that limit the effectiveness of relevant transport technologies in order to solve problems in the future and achieve progress in this area. Methodology. The theoretical analysis of scientific and technical publications, system analysis, numerical calculations, and exploratory forecasting were used. The features of the operation of high-speed transport of the 5th and 6th generation, based on the electrodynamic (electromagnetic) principle of movement and capable of reaching speeds from 200 to 60,000 km/s, are considered. Findings. The authors have established: 1) Maglev trains can become widespread in developed countries for passenger transportation and reach speeds of 600–700 km/h. They will be even cheaper, more comfortable and attractive due to new advances in high-temperature superconductivity, the use of nanoelectronics-based devices, and the solution of the issue of magnetic protection of passengers; 2) several Hyperloop lines are expected to be built for freight transportation. As operational experience is gained and safety issues of traveling in a vacuum pipeline are resolved, passenger lines may be launched. The Hyperloop will be able to reach speeds of up to 1,200 km/h; 3) Railgun transportation efficiency is expected to increase if new materials are developed and applied that would reduce ablation in extreme operating conditions. The Railgun will continue to be used in the scientific and technical sphere and in space technology; 4) it is possible to create an experimental Space Tram or its improved version if it is possible to develop the latest materials that can withstand ablation at high currents and speeds, and if there is a breakthrough in the field of high-temperature superconductivity. This development promises to significantly speed up the launch of payloads into orbit; 5) Breakthrough Starshot is unlikely to be created due to a number of technical difficulties that are far from being resolved. Originality. For the first time, the authors conducted a comprehensive analysis of technical problems in the field of ultra-high-speed transport technologies based on the electrodynamic (electromagnetic) principle of movement and proposed a forecast for the development of this transport in the next 20–30 years. Practical value. Based on the results obtained, it is possible to successfully solve the identified technical problems, which will increase the efficiency of ultra-high-speed transport technologies based on the electrodynamic (electromagnetic) principle of acceleration, movement and braking. In the near future, this will serve to speed up the introduction of freight transportation by Hyperloop-type transport and improve the acceleration devices for macrobodies such as Railgun.